THE USE OF SWIMMING AS A STRATEGIC MECHANISM FOR THE PRODUCTION OF PARESTÉSIC STIMULES IN INDIVIDUAL CAUGHT BY TRANSVERSE MYELITE (Fiep Bulletin - online, 2019)
The present study aims to use swimming as a stimulating mechanism for the development of paresthesia in a subjectaffected by transverse myelitis. Transverse Myelitis (TM) is an acute inflammatory process that affects a focal area of the spinalcord with clinical neurological manifestations in motor, sensory, and autonomic nerves. (Maciel, 2014). It is a pathology in whichan immune-mediated inflammatory process of the spinal cord occurs causing neural lesions due to complete or incomplete spinalcord transection, resulting in motor, autonomic and sensory pathway dysfunctions. (MURTHY JM, 1999; STOKES M, 2000;MUMENTHALER M., 2007). The result was that when the subject thought of the legs performing the crawl-leg movement as wellas running the leg of the butterfly swim, the hip moved. When the guy thought about his legs without doing the swinging motion ofthe swim crawl, and when he thought of the butterfly swim, his hip did not move. This caused the appearance of paresthesia in thetrunk, hip and legs. There was an interesting progression: in the first year the use of swimming caused the appearance ofparesthesia only in the feet. In the second year the use of swimming caused the appearance of paresthesia also in the hip and inthe third year the use of swimming caused the appearance of paresthesia also in the trunk. This evolution is limited so far withparesthesia reaching from the feet to the trunk. It was concluded that the use of swimming as a stimulatory mechanism for thedevelopment of paresthesia in a subject affected by transverse myelitis was a treatment that caused the onset of paresthesia andthe development of the same in a subject with this pathology. We suggest that other researchers seek to investigate in this area toimprove performance of other subjects affected by transverse myelitis can be contemplated and / or benefited.
Keywords: swimming; transverse myelitis; paresthesia